Louis-Philippe Dalembert, «vagabond jusqu’au bout de la fatigue» - Vignoli, Alessia (Il Tolomeo, 2016)
The Haitian novelist and poet Louis-Philippe Dalembert (Port-au-Prince, 1962) has developed in his works of fiction the concept of vagabondage as a literary projection of his biographical wandering through multiple spaces. The aim of this essay is to study the presence of vagabondage and its distinctive features in those novels written by Dalembert that reflect the writer’s perpetual motion: Le Crayon du bon Dieu n’a pas de gomme (1996), L’Autre face de la mer (1998), L’Île du bout des rêves (2003), Les dieux voyagent la nuit (2006). The main characters are constantly moving, they are cosmopolitan wanderers who belong to many places at the same time, just like Dalembert himself. By analyzing the representation of movement in these fictions, we will show that the notion of vagabondage is depicted by the author as a positive and meaningful opportunity for the vagabond who travels across countries, languages and cultures.